Current chemotherapy strategies for adults with IDH-wildtype glioblastoma - Bao, Jing; Sun, Rui; Pan, Zhenjiang; Wei, Shepeng (Frontiers in Oncology, 2024)
Introduction Glioblastoma, despite advancements in molecular evolution, remains incurable and has low survival rates. Currently, two of the most commonly used chemotherapy regimens are temozolomide and CCNU. This review aims to provide a comprehensive analysis of the current status of chemotherapy strategies for GBM. Methods We reviewed the published literature describing the chemotherapy regimen differences in system treatment of GBM reported in the last ten years and summarised the available information that may reveal the latest changes in chemotherapy. Results In patients with adequate functioning, temozolomide and radiation are the primary treatments for newly diagnosed GBM. We recommend postoperative radiation therapy with concurrent and adjuvant temozolomide for patients with MGMT-methylated GBM who are less than 70 years old. Combining temozolomide and lomustine with radiation therapy may be an option for younger, fit patients, but efficacy data is inconclusive. For patients with unknown MGMT methylation status, radiation therapy combined with temozolomide remains the standard of care. We recommend hypofractionated radiation and concurrent temozolomide treatment for elderly patients over 70 years old who have satisfactory performance and no significant underlying health conditions. We should tailor treatment choices to each patient’s personal preferences, previous treatments, function, quality of life, and overall care objectives. Conclusion Radiation therapy, along with temozolomide, is still the standard of care for most people with MGMT-unmethylated GBMs because there aren’t any better options, and it’s generally safe and well-tolerated. These patients have a lower overall survival rate and less benefit from temozolomide, but there are no better alternatives. Clinical trial participation is encouraged.